Nanoimaging with a compact extreme-ultraviolet laser - Kondratenko, V. V., author; Pershyn, Y. P., author; Artioukov, I. A., author; Vinogradov, A. V., author; Attwood, D. T., author; Anderson, E. H., author; Liddle, J. A., author; Chao, W., author; Rocca, Jorge J., author; Marconi, M. C., author; Menoni, C. S., author; Mancini, H., author; et al. (Colorado State University. Libraries, 2005)
Images with a spatial resolution of 120-150 nm were obtained with 46.9 nm light from a compact capillary-discharge laser by use of the combination of a Sc-Si multilayer-coated Schwarzschild condenser and a freestanding imaging zone plate. The results are relevant to the development of compact extreme-ultraviolet laser-based imaging tools for nanoscience and nanotechnology.